Characterization of laser beam intensity used for machining - Mohd Syimir Haziq, Noor Zainal (2009)
In this report, a method of characterizing the laser beam intensity was introduced. The method that had been used is the experimental method by using the laser beam machine. The main objective is to determine the laser parameters that influence the laser beam intensity. Laser intensity was characterized based on the hypothesis that intensity would be directly influenced by the geometry and heat-affected zone generated by laser. Experiments were carried out using 2k design of experiments generated in STATISTICA software. Two types of geometries: lines and spots were generated on acrylic sheet. The geometrical parameters and HAZ were measured under optical microscope and integrated image analyzer and taken as response in the STATISTICA analysis. Mathematical models were developed in STATISTICA and the most accurate models were chosen up for intensity characterization. The model show that the intensity will be characterized based on high and low term according to the laser machining parameters.